Bioactive Compounds and Antioxidant Evaluation of Methanolic Extract of Hibiscus Sabdariffa - Adusei, Stephen (IPTEK The Journal for Technology and Science, 2025)
Hibiscus Sabdariffa (Roselle) is renowned for its delicacy and healing properties. Thestudy aimed at evaluating the bioactive compounds (phytochemicals) and antioxidantactivity of leaf, stem, and calyx of roselle, extracted with methanol. Phytochemicalswere identified using numerous test methods and quantified with a UV-Vis spec-trophotometer. The screening test revealed a higher number of phytochemicals in thecalyx extract than the leaf or stem. With the quantification, the highest concentrationwas recorded in the calyx, followed by the leaf and then the stem. The antioxi-dant activity of the investigated plant was in the order of calyx>leaf>stem. Higherrecoveries, ranging between 90%-110%, was obtained for all compounds. Therefore,this study provides evidence that the leaf, stem, and calyces of roselle plants arethe probable source of antioxidants and many bioactive compounds, justifying theirethnopharmacological use in conventional medicines.